(untitled) (Fiep Bulletin - online, 2015)
On rock climbing the displacemtent changes from de horizontal to the vertical, and so the movement, which is usually realized in two supporting points, goes through a constant alternancy from four to three supporting points and vice versa, due to the use of hands and feet to sustain the body close to the wall. From this premise, the study aimed to develop a trainning methodology in artificial wall, intending to improve the rock climbing geared to beginner climbers of both genders, older than 18 years. The vertical displacements techniques are taught to climber’s from Salamandra Escola de Montanha, from Joinville, SC, in a symmetrical wall, which allows to work in a wide way the laterality and the coordination of movements, while the 70° negative inclination wall serves to training the movement continuity technique, approaching the climber from reality. The basic physical properties are develop, generally, with the learning and the training of the technique, although it’s used specific training complementary to the desired physical development. After application of the training program it was verified that the climbers whom had training at least twice a week, and practiced rock climbing at least once a week had a better improvement of feet precision movement; They where able to use better the hip positioning to a better profit of the balance point and reduce the energy consumption; as well as they could sustain the arms outstretched during de movement, using their legs to make it scroll the vertically movement even on rock. Among the climbers who trained in a less constancy, but who continued to practice rock climb at least once a week, it was possible to observed a higher difficulty in coordinating the lateral movement of feet and lateral movement of feet and hands, which are trained at the symmetrical wall and posteriorly assimilated at the 70° negative inclination wall. Besides, those climbers also demonstrated a higher difficulty in getting out the sportive position to give the movement continuity, booth in a sportive rout as the boulder, although it has been found a improvement on the triangle base utilization to the rest position and the use of hands and feet straight with a higher precision. The present methodology by providing the learning of the technique by steeps in a controlled place (indoor), showed very effective and efficient to the upgrading of the physical qualities so that the climber can be able to perform, with precision and safety movements on the vertical plan in a natural ambient.